2007
DOI: 10.1158/1078-0432.ccr-07-0587
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the Estrogen Receptor–Negative Phenotype in Breast Cancer and Restoration of Antiestrogen Response

Abstract: Purpose: In breast cancer, the presence of estrogen receptor a (ER) denotes a better prognosis and response to antiestrogen therapy. Lack of ERa correlates with overexpression of epidermal growth factor receptor or c-erbB-2. We have shown that hyperactivation of mitogen-activated protein kinase (MAPK)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 37 publications
10
96
0
Order By: Relevance
“…Yet, when fulvestrant was withdrawn from the resistant cells, ERa expression was restored and in two out of three cell lines, expression of the estrogen responsive protein Bcl-2 followed, demonstrating the presence of a functional ERa in the resistant cells, in agreement with previously published data [34]. Other studies have shown that ErbB signaling in itself can suppress ERa expression and signaling in breast cancer cells and that inhibition of such ErbB signaling can reestablish ERa mediated signaling [18,19]. This was not the case in our model system where ERa signaling, as visualized by ERa and Bcl-2 expression, was repressed by the presence of fulvestrant in the medium, but unaffected by ErbB blockade with CI-1033 upon faslodex withdrawal.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Yet, when fulvestrant was withdrawn from the resistant cells, ERa expression was restored and in two out of three cell lines, expression of the estrogen responsive protein Bcl-2 followed, demonstrating the presence of a functional ERa in the resistant cells, in agreement with previously published data [34]. Other studies have shown that ErbB signaling in itself can suppress ERa expression and signaling in breast cancer cells and that inhibition of such ErbB signaling can reestablish ERa mediated signaling [18,19]. This was not the case in our model system where ERa signaling, as visualized by ERa and Bcl-2 expression, was repressed by the presence of fulvestrant in the medium, but unaffected by ErbB blockade with CI-1033 upon faslodex withdrawal.…”
Section: Discussionsupporting
confidence: 87%
“…When fulvestrant was withdrawn from the resistant cell lines for one week prior to initiation of experiments, ERa expression was increased in all three resistant cell lines [19,35]. In the present study, such an effect of ErbB blockade with CI-1033 was mainly expected in the fulvestrant withdrawn cultures, as the ERa protein is destabilized in the presence of fulvestrant.…”
Section: Cetuximab But Not Trastuzumab or Pertuzumab Inhibits Growtsupporting
confidence: 50%
See 2 more Smart Citations
“…The cells were found to have decreased ERα levels to endocrine therapy by down-regulation of Her-2/MAPK pathway and up-regulation of ERα. Inhibition of growth factor signaling directly with U0126, the MAPK/eRK inhibitor, or indirectly by upstream inhibition of EGFR by gefitinib or HER2 through trastuzumab has resulted in functional ERα expression in several ERα-negative breast cancer cell lines with varying levels of EGFR and HER2 expression including SUM 149 (high levels of EGFR), SUM 229 (EGFR overexpressor), and SUM 190 (EGFR and HER2 overexpressor) [278]. Treatment with these compounds sensitized all the breast cancer cells studied (except SUM 149 that has high NF-κB activity) to 4-hydroxytamoxifen.…”
Section: Targeting Crosstalk Of Estrogen Receptor With Combination Ofmentioning
confidence: 99%